(3RHOI GdCUhds - (3GdYGedj, HgGA GdOjf, HgGA GdOjf GdYGedj, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g` (B1622(3es ((3eMeO Hf CHj GdaVd GdfQGbjs)
(3ChdgG (B:s
(3ChdgG(B: (3CHgi CUd jHfi Ydjg GdNWGH hChdi bhd aUd jef Edjg ChdhG GdCdHGH, (B... (3hQJHJgG Ydi NeSI efGgL(B. (3aj GdebOeGJ, hajg eWGdHs
(3BNQgG (B:s
(3BNQgG(B: (3heG Odjd JChjdg CQLM hJJQcH GdeQLMGJ eKfi hKdGK hQHGY aUGYOG, aGJHY efgG GdCbhi hGdRe eG gh CbQH Edi GdJbhi hGdMeO ddg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 102s
(3GdPQjYI, L (B12: 15(3, L (B13: 181s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs